The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4269/ajtmh.20-0983
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Infections and the Surgical Patient

Abstract: Dengue infections are increasing globally and account for significant morbidity and mortality. Severe dengue results in microvascular changes and coagulopathy that may make surgical intervention risky and the overall surgical management challenging. We outline the potential surgical manifestations and complications following dengue infections and describe the clinical, pathogenetic, diagnostic, and treatment aspects of dengue and surgical patients. The main surgical presentations were acute cholecystitis, acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 90 publications
0
21
1
Order By: Relevance
“…Direct viral invasion can also lead to acute appendicitis. Other proposed mechanisms include endotoxemia and ischemic reperfusion injury [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct viral invasion can also lead to acute appendicitis. Other proposed mechanisms include endotoxemia and ischemic reperfusion injury [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Reports from different parts of the world suggest a changing pattern in the incidence of dengue infections and associated organ involvement such as respiratory, cardiac, gastrointestinal, hepatic, renal and neurological. [2][3][4][5][6][7][8][9] In Sri Lanka, dengue epidemics occur regularly and cause considerable financial burden to the health care sector and economy of the country. 10,11 Although children are commonly affected by dengue, published data on dengue infections in children living in Sri Lanka are limited.…”
Section: Introductionmentioning
confidence: 99%
“…1 Reports from different parts of the world suggest a changing pattern in the incidence of dengue infections and associated organ involvement such as respiratory, cardiac, gastrointestinal, hepatic, renal and neurological. 2 - 9 …”
Section: Introductionmentioning
confidence: 99%
“…Another systemic review and metaanalysis conducted by Jayarajsh and colleagues in which 22 studies were included and most of them from South Asia has shown that acute abdomen sometimes the main complaint of patients with dengue infection and its cumulative prevalence was 16%. 22 Understanding these complaints in patients with dengue has multiple benefits for the patients and also for the physicians. Timely identification of such patients reduces the cost of unnecessary admission, investigations, and procedures.…”
Section: Discussionmentioning
confidence: 99%